2019
DOI: 10.1136/jnnp-2019-320442
|View full text |Cite
|
Sign up to set email alerts
|

CSF chitinase proteins in amyotrophic lateral sclerosis

Abstract: ObjectiveTo evaluate the classifier performance, clinical and biochemical correlations of cerebrospinal fluid (CSF) levels of the chitinase proteins Chitotriosidase-1 (CHIT1), Chitinase-3-like protein 1 (CHI3L1) and Chitinase-3-like protein 2 (CHI3L2) in amyotrophic lateral sclerosis (ALS).MethodsCSF levels of CHIT1, CHI3L1, CHI3L2, phosphorylated neurofilament heavy chain (pNFH) and C-reactive protein were measured by ELISA in a longitudinal cohort of patients with ALS (n=82), primary lateral sclerosis (PLS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
102
5
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 24 publications
13
102
5
3
Order By: Relevance
“…Previous cross-sectional studies have shown elevated CSF chitinase protein levels in ALS patients versus controls and no elevation in asymptomatic gene carriers compared with healthy controls. 11,12 The cross-sectional analysis in this study concurs with these findings, showing levels of ª 2020 The Authors. Annals of Clinical and Translational Neurology published by Wiley Periodicals LLC on behalf of American Neurological Association CHIT1, CHI3L1 and CHI3L2 concentrations, as well as CHIT1 activity, to be similar in healthy controls and atrisk individuals who have not yet phenoconverted (irrespective of genotype), but elevated in symptomatic ALS compared to both healthy controls and at-risk individuals.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous cross-sectional studies have shown elevated CSF chitinase protein levels in ALS patients versus controls and no elevation in asymptomatic gene carriers compared with healthy controls. 11,12 The cross-sectional analysis in this study concurs with these findings, showing levels of ª 2020 The Authors. Annals of Clinical and Translational Neurology published by Wiley Periodicals LLC on behalf of American Neurological Association CHIT1, CHI3L1 and CHI3L2 concentrations, as well as CHIT1 activity, to be similar in healthy controls and atrisk individuals who have not yet phenoconverted (irrespective of genotype), but elevated in symptomatic ALS compared to both healthy controls and at-risk individuals.…”
Section: Discussionsupporting
confidence: 88%
“…The different chitinase proteins reflect different facets of microglial and astroglial activity in ALS. [8][9][10][11][12][13][14][15] At least 10% of all cases of ALS are attributable to mutations in one of four genes: C9ORF72, SOD1, TARDBP, and FUS. Studying the carriers of these genetic mutations provides a unique opportunity to define the biochemical landscape preceding the development of clinically manifest neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…CHIT1 levels and activity in ALS have repeatedly been associated with neurofilament levels and with a faster disease progression rate in large study populations. 10,28,29,[46][47][48] Our results demonstrate the correlation between baseline CSF CHIT1 levels and neuronal damage and prognosis in MS.…”
Section: Discussionsupporting
confidence: 58%
“…Interestingly, these chitinases are neuroinflammatory biomarkers which have been previously shown to be consistently increased in CSF of ALS patients compared to neurologically healthy subjects (7,8). These results indicate that, among the unbiased signature of RNA…”
Section: Discussionmentioning
confidence: 57%
“…Recently, a study using single-cell RNA sequencing of brain tissue from an ALS mouse model reported that a specific microglial subpopulation, known as disease associated microglia (DAM), was the cell-type responsible for ALS-related microgliosis and that is enhanced by triggering receptor expressed on myeloid cells 2 (TREM2) (4). In support of this scenario, some chitinase proteins, which are known markers of microglial activation (5,6), have been consistently shown to be increased in the cerebrospinal fluid (CSF) of ALS patients (7,8).…”
Section: Introductionmentioning
confidence: 98%